1993
DOI: 10.1007/bf00201786
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of ulcerative colitis

Abstract: High-resolution magnetic resonance imaging (MRI) was used to study 16 resected rectosigmoid specimens of patients treated with total colectomy for severe ulcerative colitis (UC). Six normal colon specimens were also studied as a control group. Moreover, a parallel study of the pelvis of 24 patients with a proven diagnosis of UC was performed with the same MR system. Both in vitro and in vivo MRI findings [thickening and signal intensity (SI)] of the mural layers were qualitatively evaluated by two radiologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…10,38,40,47 Data obtained with our US activity index are in accordance with previous studies. 14,15,48,49 Low contrast enhancement of the submucosa in UC and transmural enhancement in CD was observed with fat‐suppressed MRI, and correlated with submucosal sparing in histologic specimens of UC. 9 In our study, we could often not differentiate between UC and CD on the basis of MRI findings.…”
Section: Discussionmentioning
confidence: 82%
“…10,38,40,47 Data obtained with our US activity index are in accordance with previous studies. 14,15,48,49 Low contrast enhancement of the submucosa in UC and transmural enhancement in CD was observed with fat‐suppressed MRI, and correlated with submucosal sparing in histologic specimens of UC. 9 In our study, we could often not differentiate between UC and CD on the basis of MRI findings.…”
Section: Discussionmentioning
confidence: 82%
“…Early clinical experience suggests, however, that the MR signs of inflammatory bowel disease may have a variable correlation with other estimates of inflammatory activity (1, 2). Because inflammatory bowel disease commonly improves with medical treatment alone, and endoscopic diagnosis may reveal only limited insights into the extent of inflammatory disease, clinical studies only seldom allow for a complete comparison of imaging features with histopathologic analysis (3).…”
mentioning
confidence: 99%
“…Our MRI findings in active ulcerative colitis were in agreement with those of earlier reports. 1–3 However, no earlier reports have shown loss of haustral markings in MRI. The present study showed that loss of haustral markings was a prominent finding in MRI of active ulcerative colitis and was well demonstrated in a coronal section.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that magnetic resonance imaging (MRI) is useful in determining the severity and extent of inflammatory bowel disease and in differentiating ulcerative colitis from Crohn’s disease. 1–5 We have previously shown the characteristic findings of MRI in active ulcerative colitis in children. 6…”
mentioning
confidence: 94%